Detecting Multiple Cysts in the Kidney with the Development of an Active Contour Method Based on Kidney Ultrasound (USG) Images - Mardison; Yuhandri; Tajuddin, Muhammad (International Journal of Intelligent Systems and Applications in Engineering, 2023)
This study examined digital 2-Dimensional (2D) Ultrasonography (USG) images of human kidneys. The ultrasound image was captured with an ultrasound instrument that locates items in the human body by employing sound pressure waves that fluctuate at a very high frequency (ultrasonic). This study aimed to improve kidney 2D ultrasound imaging using the Active Contour approach to find many kidney cysts. The technique used in this study is marker detection, referred to as process 1, followed by a contour initialization step, as process 2, before mapping the area of kidney cysts using the active contour method and the binary segmentation method, as process 3. The identification of renal cysts leads to the subsequent phase of RGB segmentation. The results of 43 2D ultrasound scans of the kidney from this study yielded an accuracy rate of 88.37%, with 38 images correctly identifying kidney cysts and five images incorrectly identifying kidney cysts.